An Acid Test: Facile SI‐ARGET‐ATRP of Methacrylic Acid. Issue 15 (5th July 2018) - Michl, Thomas D.; Jung, Dimitri; Pertoldi, Andrea; Schulte, Anna; Mocny, Piotr; Klok, Harm‐Anton; Schönherr, Holger; Giles, Carla; Griesser, Hans J.; Coad, Bryan R.
Abstract: Atom transfer radical polymerization (ATRP) of methacrylic acid (MAA) is challenging. Herein is reported a study of conditions for facile surface‐initiated ATRP by activator regenerated electron transfer (SI‐ARGET‐ATRP) growth of poly‐methacrylic acid (PMAA) chains from a plasma polymer surface bearing surface‐immobilized α‐bromoisobutyryl bromide, with no deoxygenation required. Factors that affect PMAA polymer growth off the surface under ARGET‐ATRP conditions are systematically investigated, such as monomer/catalyst ratio, solvent, and, most importantly, addition of salts and change of pH. While the concentrations of the copper catalyst and acid affect grafting, the most pronounced effect arises from the concentration of chloride ions. Adding 0.1m NaCl and acidifying the reaction solution to pH 3 offers the best trade‐off between reaction rate and reproducibility; yielding ≈60 nm thick PMAA graft polymers in 1 h under ambient conditions. Using this easily scalable recipe and surface analysis, the grafted polymers are verified to be pure PMAA and the graft coatings to be homogenous across a substrate of 100 mm diameter. Abstract : Homogenous, ≈60 nm thick poly‐methacrylic acid (PMAA) polymers are surface‐grafted within 1 h under ambient conditions. While the concentrations of the copper catalyst and acid affect grafting, the most pronounced effect arises from the concentration of chloride ions. Adding 0.1m NaCl and acidifying the reaction solution to pH 3 offers the best trade‐off between reaction rate and reproducibility.